Optimization of Ethanol Purification by Adsorption Process Using Silica Gel with Response Surface Methodology - Restu Sebrina Vinata; Firdiani Dwi Pratiwi; Ni Ketut Sari (G-Tech: Jurnal Teknologi Terapan, 2025)
Ethanol from the fermentation of sugar, cane, and biomass can be used as a renewable fuel, but it must be purified first with adsorption being an efficient method. This study aims to optimize ethanol purification using silica gel adsorption, investigating the effects of flow rates 0.1; 0.2; 0.3; 0.4; 0.5 ml/s and adsorbent weights 20, 30, 40, 50, 60 grams. Response Surface Methodology (RSM) with Central Composite Design (CCD) was used for optimization. The experimental results were input into Design-Expert 13 for RSM optimization using flow rate and adsorbent weight. The highest ethanol concentration of 99.8% was achieved at a flow rate of 0.1 ml/s and adsorbent weight of 60 grams. RSM optimization resulted in a concentration of 99.804% at a flow rate of 0.103 ml/s and silica gel weight of 59.818 grams. The results indicate that increasing adsorbent weight and decreasing flow rate significantly improve ethanol purity. Achieving 99.8% ethanol confirms the effectiveness of silica gel adsorption and supports the development of biofuels as renewable energy sources to reduce dependence on petroleum.